Kebijakan Politik Hukum Pemberdayaan UMKM dan Pengaruhnya terhadap Pertumbuhan Ekonomi Kota Depok - Binton Jhonson Nadapdap; Ahmad Jamaluddin (Jurnal Hukum Lex Generalis, 2025)
MSMEs in Depok City contribute significantly to the regional economy, but most businesses are still in the informal sector and are non-bankable due to low legal literacy and technical constraints in implementing OSS-RBA. The gap between Local Regulation No. 3 of 2024 and its implementation limits access to legalities such as halal certification, PIRT and intellectual property rights. This normative legal research shows that synchronizing regulations with the Job Creation Law through risk-based licensing has the potential to encourage business formalization. It is concluded that technical assistance is key to ensuring that legal transformation results in inclusive and equitable MSME growth.